Social Media Marketing and Brand Awareness for Purchasing Decisions - Benedicta Gisella S.; Rahel Noprianti S; M. Rachman Mulyandi (Cita konsultindo, 2025)
The digital era has transformed social media platforms such as Instagram, TikTok, and Facebook into primary communication and promotional tools in the business world, serving as strategic and interactive marketing channels between businesses and consumers. This study employs a descriptive qualitative method based on literature review as the foundation for data collection and analysis to examine the influence of brand awareness built through social media on purchasing decisions. The findings indicate that brand awareness gained from social media promotional activities has a significant influence on consumers' decisions to purchase products. Brand awareness has proven to be a key element in purchasing behaviour